Broun, Bettie Lee. Bettie Lee Broun to Harriet C. Johnson Broun, Petersburg, VA, May 9, 1863 - Broun, Bettie Lee (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1863)
Southern Female College May 9th 1863 My Dearest Ma, I wrote you a very short note by Mr. Harvey and have intended to wish you a long long letter ever since he left and having no way to send it I have delayed writing for that reason. Mr. Carter has kindly offered to take a letter for me and I am indeed rejoiced.
Handwritten letter from Bettie Lee Broun to her mother Harriet C. Johnson Broun. Southern Female College, Petersburg, Virginia. May 9, 1863. Original letter in poor condition with holes and tears. Date inferred. First 4 pages of letter, unknown number of pages missing. Bettie Broun writes her mother Harriet Broun and discusses the aftermath of the Battle of Fredericksburg, confederate prisoners of war, family, dresses, and reminisces about home.
Keywords: American Civil War (1861-1865); Fredericksburg, Battle of (Virginia : 1862); Jackson, Stonewall, 1824-1863; Letters; Personal correspondence; Records and correspondence; Virginia--Northumberland County; Virginia--Petersburg; Women college students; Women's colleges